0

# Factor by grouping 3-3x plus x2-x3?

Updated: 4/28/2022

Wiki User

12y ago

3 - 3x + x2 - x3 = (1 - x)(x2 + 3)

Wiki User

12y ago

Earn +20 pts
Q: Factor by grouping 3-3x plus x2-x3?
Submit
Still have questions?
Related questions

33x

### How do you solve or factor 5x squared plus 33x plus 18?

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

### How do you do this problem 12x 33x x 92- 12 x?

(12)(33x)(92-12x) (12)(33x)(92)-(12)(33x)(12x) 36432x-4752x2 if this restatement of the grouping in the original problem is correct.

### What is the solution to 33x plus 9 18?

33x + 9 = 18 ----&gt; 33x = 9 ----&gt; x = 3/11

### What is the factorization of the polynomial 3x2 plus 33x plus 54?

3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)

### What is the factor of 3x plus 21x plus 9x?

3x+21x+9x=33x. Break it apart. The factor of x is x and the factors of 33 are 3 and 11. Therefore, the factors of 3x+21x+9x are 3, 11, and x.

### What value of c makes the polynomial below a perfect square trinomial x2 8x plus c?

9x + 2 + 24x + c = 33x + 2 + c If = 0 then c = -33x - 2 if = 1 then c = -33x - 1 if = 4 then c = -33x + 2 in general, c = -33x -2 + n2 where n is any integer.

### What answer 21x plus 12x - 2 equals?

21x + 12x -2 = 0 33x -2 = 0 33x = 2 x = 2/33 x = 0.06

### 2 5x plus 1 equals 3 3x plus 7 what is x?

25x+1=33x+7 25x=33x+6 -8x=6 x=-8/6 x=-4/3

### What is the answer 21x plus 12x - 2 equals?

I'm assuming that your solving for X. 21x + 12x - 2 = 0 33x - 2 = 0 33x = 2 x = 2/33 x =.06

### What are the ratings and certificates for 33X Around the Sun - 2005?

33X Around the Sun - 2005 is rated/received certificates of: UK:15

### Factor 7x2 plus 33x-10?

7(x^2)+33x-10 This is the way I would approach this problem. Find the factors of the first and last number: Factors of 7: 1,7 Factors of -10: -10,-5,-2,-1,1,2,5,10 Set up the two quantities: (x +/- __)(7x +/- __ ) Figure out which factors of -10 when multiplied with the factors of 7 then added together will equal +33: 5(7)+(-2)=33 Therefore: (x+5)(7x-2) Double check answer by foiling: (x+5)(7x-2)=7(x^2)-2x+35x-10 7(x^2)+33x-10